2023
DOI: 10.1177/00207640231162277
|View full text |Cite
|
Sign up to set email alerts
|

Religious coping, care burden and psychological distress among informal caregivers of COVID-19 patients: Results of a cross-sectional survey in Pakistan

Abstract: Background: There is a complex relationship between health and religiosity. People may use religion to cope with difficulties and uncertainties in their life – such as induced by the COVID-19 pandemic. Aims: The purpose of this study is to investigate the relationship between religious coping, care burden and psychological distress among caregivers during COVID-19 in Pakistan. Method: We conducted a cross-sectional survey in Pakistan. We used the Religious Coping Scale (RCOPE), Care Burden Scale (CB), and Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This finding was initially surprising, as a majority of research on the relationship between spirituality or religiosity and anxiety in times of COVID-19 pandemic supported the protective character of spirituality or religiosity. However, others found no significant correlation between religiosity and anxiety (15,26) or even found that negative religious coping elevates anxiety (28,29). Koenig ( 16) also highlights the inconsistency and heterogeneity of findings on the relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was initially surprising, as a majority of research on the relationship between spirituality or religiosity and anxiety in times of COVID-19 pandemic supported the protective character of spirituality or religiosity. However, others found no significant correlation between religiosity and anxiety (15,26) or even found that negative religious coping elevates anxiety (28,29). Koenig ( 16) also highlights the inconsistency and heterogeneity of findings on the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also did not find a significant association for COVID-19-related fear ( 26 ) and exhaustion ( 27 ). However, further authors found that negative religious coping elevated anxiety ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 98%
“…However, the dynamics of religious coping and mental health are complex, with the burden of caregiving for thalassemia generally categorized as moderate, yet exacerbated by financial and caregiving responsibilities (16,19). Negative coping strategies can exacerbate anxiety, whereas positive strategies can significantly improve overall well-being (18)(19)(20)(21)(22)(23). This study aims to explore the intricate relationship between caregiver burden, religious coping, and the mental health of caregivers of thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%